Morphology-controlled CH3NH3PbI3 films by hexane-assisted one-step solution deposition for hybrid perovskite mesoscopic solar cells with high reproductivity. Issue 45 (14th October 2015) - Lin, Na; Qiao, Juan; Dong, Haopeng; Ma, Fusheng; Wang, Liduo
Abstract : Morphology-controlled perovskite films were realized by n -hexane to promote crystallization of CH3 NH3 PbI3, thus improving their thermal stability and performance of the perovskite solar cells. Abstract : The morphology and crystal structure of perovskite films are critical for achieving high-performance perovskite solar cells; however in most cases, the conventional one-step solution deposition method hardly yields a homogeneous perovskite film over a large area, especially for CH3 NH3 PbI3 . Here, we propose a facile and environmentally friendly hexane-assisted one-step solution approach for dense and uniform CH3 NH3 PbI3 thin films. According to the phase diagram of immiscible liquids, n -hexane was chosen as the assistant solvent to speed-up the evaporation of the main solvent N, N -dimethylformamide (DMF) during the solution deposition process, thus significantly promoting the nucleation and crystallization process of CH3 NH3 PbI3 perovskite. The as-prepared CH3 NH3 PbI3 films demonstrated a uniform and dense morphology, and enhanced light absorption in a long-wavelength range. In particular, such n -hexane treatment could help eliminate the residual DMF and greatly improve the thermal stability of the obtained perovskite films. The full solution-processed CH3 NH3 PbI3 solar cells using n -hexane treatment exhibited a maximum power conversion efficiency of 11.7% and average efficiencies of 11.3 ± 0.4% under standard AM 1.5 conditions in comparison with 7.0 ± 0.4% of the conventional cells. The recombination resistance of the cells increased nearly 5 times by using n -hexane. These results suggest that this hexane-assisted one-step solution approach is promising for controlling the crystallization process of perovskites to achieve high-performance perovskite solar cells.